Analysing the Current State of a Warehouse -A Framework Based on VSM, Activity Profiling and Benchmarking - Wessman,Ida; Bärring,Maja (2014)
The 21st century has brought significant changes to the market. The ability to deliver the right product at the right time with the right price is no longer just crucial for a company’s competitive success, in the long-term perspective it will decide if the company will survive on the market at all. A warehouse has a major impact on a firm’s service levels, response times and overall cost. To meet customer requirements and to keep up with the ever-changing market there is a need of improving warehouse operations. For this study, a framework with Value Stream Mapping (VSM) in combination with Activity Profiling and Benchmarking is developed. VSM visualises the flow of material and information in a process and it is a concept commonly used for industrial improvements. The use of VSM in warehouses is however lagging behind. Activity Profiling is used to understand the activities and operations connected to a warehouse and Benchmarking is the process of gathering and sharing assessments of performance. It is believed that the combination will give a more comprehensive result compared to applying only one of the concepts. To meet the purpose of the thesis a case company is used, Alfa Laval in Lund. Alfa Laval has two warehouses at the site that will be used to examine and evaluate the framework. The purpose of the study is to investigate how the framework is applicable to present a current situation analysis of a warehouse. The aim of combining the three different concepts is to create a framework that takes several aspects into account in order to establish a fair picture of the warehouse state. For this study “the research process onion” serves as an outline for the methodology. Data collection is in the centre of the model and the core of this method. Interviews, observation and secondary data have been used for the data collection to receive a fair picture of the current state in the two warehouses at Alfa Laval. With the framework data are analysed and improvement areas are identified. A proposal is given of where Alfa Laval could build a new warehouse at the site. It is then analysed how the three concepts contributed to given recommendations and identified improvements. The three concepts complement each other in many ways and it is recommended to use them together when evaluating the current warehouse state and to find areas of improvement.
Keywords: Value Stream Mapping; Activity Profiling; Benchmarking; Warehousing; Warehouse design; Lean warehouse; Distribution centre; Warehouse management